A comparative study of the ability of recombinant oncolytic adenovirus, doxorubicin and tamoxifen to inhibit the proliferation of breast cancer cells. Issue 20 (23rd September 2022) - Li, Shanzhi; Li, Zhuoxin; Li, Yiquan; Zhu, Yilong; Han, Jicheng; Li, Wenjie; Jin, Ningyi; Fang, Jinbo; Li, Xiao; Zhu, Guangze
Abstract: In this study, we compared the inhibitory effects of recombinant oncolytic adenovirus (Ad‐apoptin‐hTERTp‐E1a, Ad‐VT) with that of doxorubicin (DOX), a first‐line chemotherapy drug, and tamoxifen (TAM), an endocrine therapy drug, on the proliferation of breast cancer cells. We found that Ad‐VT could effectively inhibit the proliferation of breast cancer cells ( p < 0.01); the inhibition rate of Ad‐VT on normal mammary epithelial MCF‐10A cells was less than 20%. DOX can effectively inhibit the proliferation of breast cancer cells and also has a strong inhibitory effect on MCF‐10A cells ( p < 0.01). TAM also has a strong inhibitory effect on breast cancer cells, among which the oestrogen‐dependent MCF‐7 cell inhibition was stronger ( p < 0.01), At higher concentrations, TAM also had a high rate of inhibition (>70%) on the proliferation of MCF‐10A cells. We also found that both recombinant adenovirus and both drugs could successfully induce tumour cell apoptosis. Further Western blot results showed that the recombinant adenovirus killed breast cancer cells through the endogenous apoptotic pathway. Analysis of the nude mouse subcutaneous breast cancer model showed that Ad‐VT significantly inhibited tumour growth (the luminescence rate of cancer cells was reduced by more than 90%) and improved the survival rate of tumour‐bearing mice ( p < 0.01). Compared with DOX and TAM, Ad‐VT has a significant inhibitory effect on breast cancer cells, but almost no inhibitory effect on normal breast epithelial cells, and this inhibitory effect is mainly through the endogenous apoptotic pathway. These results indicate that Ad‐VT has significant potential as a drug for the treatment of breast cancer.